Burn wound conversion: clinical implications for the treatment of severe burns - Asuku, Malachy; Shupp, Jeffrey W (Journal of wound care, 2023)
The identification of novel treatments for severe burn wounds relies on accurate clinical assessments of the extent of injury. However, evaluation of burn wound depth can be challenging due to the tendency for burn wounds to progress over time in a little-understood process known as 'burn wound conversion'. Local factors affecting the burn wound, such as inflammation, oxidative stress-induced tissue damage, vasostasis and bacterial infections, lead to increased cell death by apoptosis or oncosis, while systemic events may promote burn wound conversion. Acute shock, metabolic derangements, age or immunomodulation can modify cytokine secretion, lower immune responses, decrease blood flow or cause bacterial infection at the burn wound site. Therefore, therapeutic approaches targeting specific mechanisms that reduce cell death, improve wound reperfusion and promote tissue regrowth should favourably enhance burn wound healing, and long-term functional and aesthetic outcomes. Our current understanding of these mechanisms mostly comes from animal studies, underscoring the need for extensive research in humans. A streamlined approach would be to investigate the parallels in other disease states that exhibit ischaemia and potential reperfusion, such as ischaemic stroke and myocardial infarction. Moreover, in view of the limited knowledge available on the subject, the need exists for further clinical research into burn wound conversion and novel target pathways to ameliorate its effects. This review describes events that affect the viability of cells at the burn wound site resulting in burn wound conversion, and identifies potential targets for clinical interventions that may diminish burn wound conversion.